Degradation of liquid phase N, N-dimethylformamide by dielectric barrier discharge plasma: Mechanism and degradation pathways. (December 2019) - Sang, Wenjiao; Cui, Jiaqi; Mei, Longjie; Zhang, Qian; Li, Yunyang; Li, Danyi; Zhang, Wanjun; Li, Zhixuan
Abstract: The degradation of liquid phase N, N-dimethylformamide (DMF) using the dielectric barrier discharge (DBD) plasma was studied in the present study. The results showed that 1000 mg L −1 DMF could be degraded by DBD plasma under different input power, treatment time and initial pH values of aqueous solution. After 40 min with DBD plasma discharge, 52.2% degradation efficiency was achieved at DMF concentration of 1000 mg L −1 with an input power of 16.19 W under initial pH of 11.14 in aqueous solution, and the energy efficiency of the system was 13.2 mg kJ −1 . The removal efficiency decreased with the presence of radical scavenger, manifesting that OH plays a critical role in the degradation process. The value of TOC in DMF aqueous solution decreased from 790 mg L −1 to 507 mg L −1 in 40 min, which indicated that DBD plasma has the ability to mineralize a portion of DMF in liquid directly. Additionally, the analysis of FTIR, HPLC and the small molecular organic compounds before and after the DBD plasma degradation indicated that the intermediates of DMF in degradation process were N-methylformamide, methanol, formaldehyde and formic acid, which were finally mineralized into ammonia nitrogen, CO2 and H2 O. Moreover, the possible degradation mechanism and pathways were proposed. Graphical abstract: Image 1 Highlights: DMF in liquid phase can be degraded by DBD plasma is illustrated to be feasible. Various operating parameters on DMF degradation were studied. OH played a major role in the process of DMF degradation by DBD plasma treatment. The possible degradation mechanism and pathways were proposed.